Konstruksi Wanprestasi dalam Perikatan Digital: Analisis Kekosongan Norma dan Model Digital Contractual Liability dalam Ekosistem Fintech di Indonesia - Lulu Syakirah Alatas; Annisaul Malamah; Rizky Dwi Pradana (Jurnal Hukum Lex Generalis, 2026)
The development of financial technology (fintech) has shifted contractual relationships from bilateral to multi-party digital arrangements. This transformation raises new issues in understanding breach of contract, which can no longer be fully explained by classical contract law. The involvement of digital platforms as intermediaries adds complexity, particularly in determining liability and evidentiary aspects. This study aims to examine the construction of breach of contract in digital relationships and to identify normative gaps in Indonesian contract law. It uses a normative legal method with statutory and conceptual approaches. The findings show that the legal framework does not adequately regulate platform liability and still faces weaknesses in electronic evidence. Therefore, a reconstruction of contract law through a more adaptive digital contractual liability concept is necessary.